1996
DOI: 10.1038/bjc.1996.371
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of the arotinoid Ro 40-8757 in human gastrointestinal and pancreatic cancer cell lines: combinations with 5-fluorouracil and interferon-α

Abstract: Summary The arotinoid Ro 40-8757 was previously shown to inhibit the growth of a variety of human cancer cell lines derived from breast, lung and uterus. In view of the high incidence of human digestive cancers, and the slow progress in the development of new therapy, we examined in this paper several combinations between the new arotinoid Ro 40-8757, 5-fluorouracil (5FU) and interferon a-2a on the growth of nine human cancer cell lines derived from the gastrointestinal and pancreatic system. Half-maximal inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…This compound exhibited a significant degree of activity also at relatively low concentrations and against a wide panel of BL cell lines, regardless of the geographic origin of primary lymphoma and the type of c-myc-activating translocation. These findings are in keeping with previous observations demonstrating that Ro 40-8757 was one of the most active retinoids in inhibiting the growth of a variety of cell lines derived from carcinomas of different origin Uchida et al, 1994;Louvet et al, 1996). Moreover, consistent with what observed in other cellular systems, the drug did not induce any cell cycle phase-specific accumulation of BL cells Uchida et al, 1994;Louvet et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…This compound exhibited a significant degree of activity also at relatively low concentrations and against a wide panel of BL cell lines, regardless of the geographic origin of primary lymphoma and the type of c-myc-activating translocation. These findings are in keeping with previous observations demonstrating that Ro 40-8757 was one of the most active retinoids in inhibiting the growth of a variety of cell lines derived from carcinomas of different origin Uchida et al, 1994;Louvet et al, 1996). Moreover, consistent with what observed in other cellular systems, the drug did not induce any cell cycle phase-specific accumulation of BL cells Uchida et al, 1994;Louvet et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…ATRA and 9cRA have previously been reported to have anti-proliferative effects and to modulate differentiation in pancreatic cancer cells (Rosewicz et al, 1995;Bold et al, 1996;Louvet et al, 1996). We have shown that they can also act as potent apoptosis-inducers (Pettersson et al, 2000), and in this study we have further elucidated the mechanisms behind this finding.…”
Section: Discussionmentioning
confidence: 50%
“…Responsiveness to retinoids in pancreatic cancer cells has previously been reported by different groups (Rosewicz et al, 1995;Bold et al, 1996;Louvet et al, 1996). A phase II trial of 13-cis retinoic acid and interferon-a in patients with advanced pancreatic carcinoma has also been completed and promising results with one partial remission and 14 out of 22 patients with stable disease for a median duration of 5 months were reported (Brembeck et al, 1998).…”
mentioning
confidence: 83%
“…Differential effects have also been shown in melanoma and colon cancer cells (Kane et al, 1996;Danielsson et al, 1999). In pancreatic cancer cells, responsiveness to both retinoids and vitamin D analogues have been reported previously (Rosewicz et al, 1995;Bold et al, 1996;Kawa et al, 1996;Louvet et al, 1996;Zugmaier et al, 1996;Colston et al, 1997). However, those studies have mainly assessed inhibition of cell growth and apoptosis has not been examined.…”
Section: Discussionmentioning
confidence: 99%